Sépultures secondaires à crémation - Henri Duday (Les Nouvelles de l’Archéologie, 2019)
Over the past thirty years, the study of secondary burials by cremation has grown considerably in France in the context of the development of archaeo-anthropology. Quantitative osteology, and especially weight data, allow a better reading of the successive times that are cremation on the stake and the collection of burned bones. The systematic research of osteological links and exclusionary relationships also provides irreplaceable informations on the existence of sites reserved for the construction of bonfires, on the relative chronology of cremations that followed one another, on the cleaning of cremation areas, on the transfer of burnt bones to the grave and their deposition inside it.